The Arequita Formation (Lower Cretaceous): Petrographic features of the volcanic facies In the Laguna Merín Basin, east Uruguay (Latin American Journal of Sedimentology and Basin Analysis, 2021)
The southeastern border of the Laguna Merín Basin (Rocha Department, EastUruguay) consists of Mesozoic volcanic deposits of the Puerto Gómez and Arequitaformations, overlain by a sedimentary cover of Cenozoic and recent deposits. Wellpreservedlava flow and pyroclastic deposits have been identified in the Arequita Formationafter detailed mapping (1.50.000) in Sierra de los Ajos region. The present study focuseson the petrographic characterization of this felsic volcanism, with special emphasis onthe pyroclastic units. Differences in the structural and petrographic distribution of thesevolcanic units are related to the N20ºE trending India Muerta Lineament. East of thislineament, SiO2-rich rhyolites and pyroclastic deposits (ignimbrites) are present whereasto the west, the volcanic rocks are mainly represented by basic to felsic lavas. Basedon petrographic features and regional distribution, explosive mechanisms have beenassigned to some of the volcanic units, interpreted as pyroclastic flow and pyroclasticsurge deposits.